Interpretable machine learning for optimization of ultrasound-assisted polysaccharide extraction using natural deep eutectic solvents: From yield enhancement to structural and antioxidant activity validation - Shulu Zhang; Jingting Han; Ruichen Gao; Yeqing Xu; Zheng Feng; Xinhui Huang; Yinze Zhong; Qingxia Wang; Xinran Yu; Siyu Chang; Meiting Jiang; Zhibin Wang; et al. (Bioresource Technology, 2026)

Anomalous mercury isotopic composition highlights the essential role of terrestrial erosion in forming cold seeps in the continental margin of the South China Sea - Xiaoming Sun; Ruichen Jia; Runsheng Yin; Xin Yang (Journal of Asian Earth Sciences, 2026)

Dynamic social disparities in the U.S. electric vehicle charging infrastructure system - Ruichen Ma; Mingming Guan; Dingkang Teng; Xiong Yang; Chengxiang Zhuge (Transportation Research Part D: Transport and Environment, 2026)

Personalized thermal comfort elicitation for human-centric building environments with low-cognitive-load conversational AI - Yizheng Li; Huan Zhao; Guandong Su; Yang Meng; Yongan Zhang; Yan Li; Ruichen Ding; Zhangxing Chen; Jinyue Yan (Building and Environment, 2026)

Physics-Informed Deep-Learning Prediction of Tropical Cyclone Wind Size in the Western North Pacific - Ruichen Guo; Jing Xu; Chi Yang; Mingzhu Zhou (Journal of Meteorological Research, 2026)

Dataset of China Kuroshio Extension Observatory (CKEO): Moored Buoy Observations in the Kuroshio–Oyashio Transition Zone - Zhaohui Chen; Yueqi Zhang; Ruichen Zhu; Zhongxiang Fan; Jia-Zhen Wang; Xin Ma; Guoqing Ren; Haiyuan Yang; Lixiao Xu; Xiaopei Lin; Lixin Wu (Advances in Atmospheric Sciences, 2026)
The Kuroshio–Oyashio Transition Zone (KOTZ) serves as a vital dynamic interface between the warm Kuroshio Extension and the cold Oyashio Current. However, severe sea conditions with strong ocean currents, winds and waves pose challenges for sustained in situ observations of both oceanic and atmospheric variables. This paper introduces the China Kuroshio Extension Observatory (CKEO), a moored observatory program designed for long-term observations in the KOTZ. We provide a dataset of meteorological and oceanographic properties, including sea surface wind, air temperature, atmospheric pressure, relative humidity, sea surface temperature, sea surface salinity, ocean currents in the upper 100 m, and temperature profile in the upper 500 m. The CKEO, which began operations in 2019, provides a continuous air–sea observational dataset of the KOTZ to the scientific community and advances the understanding of multiscale physical processes in this region.

A global insight into integration of metro and electric vehicle charging stations - Dingkang Teng; Justin Hayse Chiwing G. Tang; Ruichen Ma; Xiong Yang; Chengxiang Zhuge (Sustainable Cities and Society, 2026)

Femtosecond laser-fabricated defect-rich PtRe alloy clusters for enhanced alkaline hydrogen evolution - Xianze Zhang; Junwen Xiong; Zhiyi Sun; Ruichen Lu; Zikang Su; Chen Zhang; Qimiao Zhu; Shilong Yuan; Lan Jiang; Shengjie Xia; Liquan Sun; Xingdong Wang; et al. (Chemical Engineering Journal, 2026)

Postharvest application of plasma-activated water delays anthracnose symptom development in apples - Yingman Gao; Ruichen Sha; Guihuan Wei; Lingling Yang; Yupan Zhu; Yudong Liu; Ruonan Ma; Zhen Jiao; Bing Li (Postharvest Biology and Technology, 2025)

Self-templated fabrication of heterogeneous F doped NiCo-alkoxides/NiCo hydroxides yolk-shelled spheres with enhanced performance for supercapacitors - Xu Zhang; Ying Chen; Shuxian Song; Lu Song; Ruichen Zhai; Yulan Meng; Shaojie Li; Lijuan Wei; Xutong Yang; Anmin Liu (Chemical Engineering Journal, 2025)

Identification of active sites for formaldehyde oxidation on mesoporous Pt/CeO2 catalyst at ambient temperature and low humidity - Ruichen Wang; Chao Yu; Juanjuan Gong; Qingfa Su; Hui Chen; Canyan Yang; Shaodi Sun; Zhiwei Huang; Huazhen Shen; Huawang Zhao; Bihong Lv; Xiaomin Wu; et al. (Fuel, 2025)

Serum polychlorinated biphenyls as a risk factor for MASLD: Exploring the association and underlying mechanisms - Ruichen Yang; Qingqing Jiang; Wentao Liu; Furong Wang; Shiyi Cao (Science of The Total Environment, 2025)

Rice cultivation and its environmental and social contexts at the Shimao site, Northwest China - Shu Liu; Ruichen Yang; Zhouyong Sun; Jing Shao; Zhikun Ma (Archaeological and Anthropological Sciences, 2025)

Ecological and Evolutionary Factors Contribute to the Uneven Diversification of Firs in the Northern Hemisphere - Qiaoping Xiang; Jie Yang; David S. Gernandt; Tongxin Ye; Ling Yang; Jiaming Pan; Ruichen Xiang; Cheng Zhao; Koh Nakamura; Xianchun Zhang; Yongbo Liu; Ran Wei (Journal of Biogeography, 2025)
Aim The Northern Hemisphere harbours the greatest diversity of temperate plants on Earth, with East Asia having the highest species richness compared with North America and Europe. When and how this uneven diversification pattern emerged remains unclear. Here, we use a conifer genus that forms extensive forests in the Northern Hemisphere to explore a fundamental question in ecology and evolution: what processes underlie temperate biodiversity through time and space? Location The Northern Hemisphere. Taxon Abies . Methods To reconstruct a well‐supported framework for estimating diversification rate, we performed phylogenetic analyses using concatenation and coalescent methods based on 58 fir taxa and 56 nuclear single‐copy genes. Niche evolution was explored using species occurrence data and environmental factors based on the l1ou model. Multiple regression was carried out to identify correlations between species richness and environmental variables at global and regional scales, to evaluate factors of species diversity preference, and potentially to explain the evolutionary history of firs. Results We identified East Asia as having the highest species diversity and speciation rate. Two clade‐specific niche shifts corresponding with the distribution of firs were detected, one in the Himalaya‐Hengduan Mountains ( c. 12.2 Ma) and the other in the Mexican highlands ( c. 14.3 Ma), but none in the Euro‐Mediterranean region. Fir species richness increased with cool temperatures both globally and regionally. Seasonal precipitation showed significant positive correlation to species richness on a global scale and in North America and the Euro‐Mediterranean region. Soil factors showed significant trends and moderate correlations with species richness in the Himalaya‐Hengduan Mountains and Mexican highlands. Main Conclusions Our results indicate that modern firs prefer cool climates with seasonal rainfall. East Asian firs experienced niche shifts with the Himalayan orogeny in the Middle Miocene. Novel heterogeneous habitats due to changes in topography and the establishment of a monsoon climate, accompanied by niche shift, can account for the high speciation of firs in East Asia. A similar process is found in the Mexican highland firs. In contrast, cold–dry continental climate in North America since the late Paleogene and the lack of seasonal rainfall and relatively stable topography in the Euro‐Mediterranean region are the main limiting factors for fir diversification. Our study rejects the ‘clade age’ hypothesis but supports the hypothesis that niche shift related to high diversification rate triggered by environmental heterogeneity underlies the uneven species diversity of the Northern Hemisphere.

Palbociclib inhibits the progression of head and neck cancer and improves the Cetuximab response under specific condition in vitro and in vivo - Ruichen Li; Qi Wang; Yang Zhao; Yi Zhu; Xiaoshen Wang (Molecular Biology Reports, 2024)

Genomic selection on ear height, plant height and grain yield in the primary testing stage of maize hybrids - Xinying Kong; Shuwen Ji; Yubo Liu; Xuecai Zhang; Meiling Liu; Chen Yue; Ruichen Yang; Cong Li; Xiaomei Dong; Ao Zhang; Yanye Ruan (Euphytica, 2024)

Nomogram to predict central lymph node metastasis in papillary thyroid carcinoma - Dehui Qiao; Xian Deng; Ruichen Liang; Xu Li; Rongjia Zhang; Zhi Lei; Hui Yang; Xiangyu Zhou (Clinical & Experimental Metastasis, 2024)

A multi-target and responsive nanoplatform (MM/ZnS/ATV) combining H2S and atorvastatin for enhanced atherosclerosis therapy - Yinhong Xie; Mengchen Chi; Ruichen Dong; Sui Wu; Jinming Yang; Qin Wang; Junying Chen; Yajun Weng (Chemical Engineering Journal, 2024)

Combined InSAR and optical dataset unravelling the characteristics of hillslope erosion in burned areas in Xichang, China - Xichao Cao; Kun He; Xiewen Hu; Gang Luo; Yonghao Zhou; Ruichen Zhou; Ying Yang; Tao Jin (CATENA, 2024)

Mechanistic insight into the catalytic CO oxidation and SO2 resistance over Mo-decorated Pt/TiO2 catalyst: The essential role of Mo - Chao Yu; Canyan Yang; Ruichen Wang; Geyu Dai; Hui Chen; Zhiwei Huang; Huawang Zhao; Zuoming Zhou; Xiaomin Wu; Guohua Jing (Chemical Engineering Journal, 2024)

Engineering stable Cu+-Cu0 sites and oxygen defects in boron-doped copper oxide for electrocatalytic reduction of CO2 to C2+ products - Canyan Yang; Ruichen Wang; Chao Yu; Jinhua Xiao; Zhiwei Huang; Bihong Lv; Huawang Zhao; Xiaomin Wu; Guohua Jing (Chemical Engineering Journal, 2024)

DEHP and DBP, common phthalates, induce glucose metabolism disorders in rats via oxidative damage of PI3K/Akt/GLUT4 signaling - Liping Li; Lingyan Huang; Ruichen Lei; Pengju Zhang; Yi Yang; Herong Liu; Yuhong Zhang (Environmental Pollution, 2024)

Pinocembrin Inhibits P2X4 Receptor–Mediated Pyroptosis in Hippocampus to Alleviate the Behaviours of Chronic Pain and Depression Comorbidity in Rats - Runan Yang; Jingjian Yang; Zijing Li; Ruichen Su; Lifang Zou; Lin Li; Xiumei Xu; Guilin Li; Shuangmei Liu; Shangdong Liang; Changshui Xu (Molecular Neurobiology, 2022)

Araneose Ti3+ self-doping TiO2/SiO2 nanowires membrane for removal of aqueous MB under visible light irradiation - Zhao Gao; Hanpei Yang; Jingtao Mao; Li Kang; Ruichen Zhang; Siqi Chai; Junming Wu; Wei Li (Environmental Science and Pollution Research, 2020)

Historical record of anthropogenic polycyclic aromatic hydrocarbons in a lake sediment from the southern Tibetan Plateau - Ruiqiang Yang; Ruichen Zhou; Ting Xie; Chuanyong Jing (Environmental Geochemistry and Health, 2018)